1984
DOI: 10.1111/j.1464-5491.1984.tb01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer Based Learning and Assessment for Diabetic Patients

Abstract: A comparatively inexpensive microcomputer-based system of programmed diabetic instruction is described, matched to an interactive knowledge assessment questionnaire with or without prescriptive feedback. This provides an educational and assessment package for newly diagnosed and established diabetics, with additional analytical potential. The system is well accepted, demonstrates major areas of defective knowledge and allows cost-effective handling of large numbers of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Costs associated with the interventions were reported by 9 studies (Table 3) 9,11,15–17,19,26–28 ; most authors did not report itemized costs. The majority of the articles reported the costs of the systems used to conduct the interventions, which ranged from $5.00 per patient to $6,340 for the complete system (i.e., computer, PDA, telemedicine, etc.).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Costs associated with the interventions were reported by 9 studies (Table 3) 9,11,15–17,19,26–28 ; most authors did not report itemized costs. The majority of the articles reported the costs of the systems used to conduct the interventions, which ranged from $5.00 per patient to $6,340 for the complete system (i.e., computer, PDA, telemedicine, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the articles reported the costs of the systems used to conduct the interventions, which ranged from $5.00 per patient to $6,340 for the complete system (i.e., computer, PDA, telemedicine, etc.). Lastly, none of the studies from the internet category, 4 of the 7 studies in the telephone category, 11,15,16,19 and 5 of the 14 studies in the computer‐assisted integration of clinical information category reported costs associated with the interventions 9,17,26–28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 ' 4 In brief, the interactive computer teaching (ICT) with either direct system-patient interaction 1 or an inter-program consists of sequences of text and animated graphics mediate operator. 2 Our study was undertaken in an attempt dealing with general diabetes concepts, hypoglycemic drug to use the maximum potential of a computer in learning; i.e., action, glucose control, blood and urine monitoring, com- plications, diet, and foot care.…”
mentioning
confidence: 99%